2014
DOI: 10.1371/journal.pone.0087910
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial to Evaluate Two Doses of an Intra-Articular Injection of LMWF-5A in Adults with Pain Due to Osteoarthritis of the Knee

Abstract: ObjectiveThe Low Molecular Weight Fraction of 5% human serum Albumin (LMWF-5A) is being investigated as a treatment for knee pain from osteoarthritis.MethodsThis was a multicenter randomized, vehicle-controlled, double-blind, parallel study designed to evaluate the safety and efficacy of two doses of an intra-articular injection of LMWF-5A. Patients with symptomatic knee osteoarthritis were randomized 1∶1∶1∶1 to receive a single 4 mL or 10 mL intra-articular knee injection of either LMWF-5A or vehicle control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 25 publications
1
62
0
Order By: Relevance
“…If this effect were uniform for all OA patients, a simple subtraction might be considered the appropriate manner of dealing with this confounding factor. This appears not to be the case, as demonstrated in the clinical trial testing IA injections of the low molecular weight fraction of human serum albumin for OA [4, 5]. In this study the amelioration of pain with physiological saline was much less pronounced in patients with the most severe OA (KL 4 patients).…”
Section: Nociceptive and Neuropathic Pain In Oamentioning
confidence: 58%
See 2 more Smart Citations
“…If this effect were uniform for all OA patients, a simple subtraction might be considered the appropriate manner of dealing with this confounding factor. This appears not to be the case, as demonstrated in the clinical trial testing IA injections of the low molecular weight fraction of human serum albumin for OA [4, 5]. In this study the amelioration of pain with physiological saline was much less pronounced in patients with the most severe OA (KL 4 patients).…”
Section: Nociceptive and Neuropathic Pain In Oamentioning
confidence: 58%
“…In recent years, intra-articular (IA) knee joint injections have been used to relieve symptoms of this condition. These have succeeded to varying degrees either with sodium hyaluronate preparations [1, 2], platelet-rich plasma (PRP) [3], or with a low molecular weight fraction (< 5kDa) of human serum albumin (LMWF-5A) [4, 5]. In all of these studies, the control arm was injection of the same volume of sterile physiological saline ( i.e .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety and efficacy of LMWF5A was evaluated in 329 patients with moderate to severe OA of the knee in the multicenter, randomized, vehicle-controlled, double-blind, phase III SPRING study (ClinicalTrials.gov identifier NCT01839331) [8]. The protocol for the SPRING study was approved by the institutional review boards from SUNY-Buffalo Health Sciences and Liberty IRB (Deland, FL, https://www.libertyirb.com/) and complies with the code of ethics of the World Medical Association.…”
Section: Spring Study Synovial Fluid Sample Preparation and Proteomicmentioning
confidence: 99%
“…[4][5][6][7] A pivotal phase III randomized controlled trial showed that a single intraarticular injection of LMWF-5A was effective in reducing pain in adults with osteoarthritis of the knee and was safe and well tolerated. 8 This study investigated the safety and efficacy of 3 biweekly intraarticular injections of LMWF-5A in osteoarthritis of the knee.…”
Section: Preliminary Trial Of Intra-articular Lmwf-5a For Osteoarthrimentioning
confidence: 99%